Facet analysis as conceptual modeling of hypertexts: methodological proposal for the management of semantic content in digital libraries - Lima, Gercina Angela Borém Oliveira; Maculan, Benildes Coura Moreira dos Santos (Qualitative and Quantitative Methods in Libraries; Vol 4 No 3 (2015): September 2015 Issue, 2017)
This study aims at the construction of a semantically structured conceptual model to help the organization and representation of human knowledge in hypertextual systems, based on the Theory of Facet Analysis and Conceptual Map. A second step in this study is the application of the semantic model to create a prototype called Hypertext Map (Mapa Hipertextual - MHTX) which will be used to implement the BTDECI – UFMG (Thesis and Dissertation Library of UFMG´s School of Information Science). Facet analysis was used to categorize the index terms, and established the relationship among them expressed by the links. It was chosen a single knowledge unit, namely a doctoral thesis on the own area of subject analysis (NAVES, 2000) to construct a conceptual model prior to the technological implementation of its prototype..